MEMBACA KEMBALI PANDANGAN MORALITAS POSTMODERNISM UNTUK KONTEKS PENDIDIKAN KRISTEN (RE-READING THE WORLDVIEW OF POSTMODERNISM MORALITY FOR THE CONTEXT OF CHRISTIAN EDUCATION) - Recky Pangumbahas; Oey Natanael Winanto (QUAERENS: Journal of Theology and Christianity Studies, 2021)
One of the most important elements of postmodernity is the growing awareness of the diversity and potential incommensurability of the various forms of cultural life that sustain groups and individuals and addresses the postmodernist denial that postmodernism is inherently apathetic or hostile to social or political action. Postmodernism is a reaction to the epistemological ideals of modernity. Postmodernism is based on a limited human point of view, and thus becomes a prisoner of its own subjectivity, resulting in two main characteristics, namely pluralism and relativism. This study analyzes the postmodern view that is implemented in Christian education in Indonesia. The method used in this article is a literature study by using philosophical biblical glasses to analyze postmodern views. The result is that postmodern moral education (such as transcendentalism and idealism) has some useful and some negative aspects that should be considered for planning moral education and curriculum development for Christian education in Indonesia. Satu elemen paling penting dari postmodernitas adalah tumbuhnya kesadaran akan keragaman dan potensi ketidakterbandingan dari berbagai bentuk kehidupan budaya yang menopang kelompok dan individu dan membahas penolakan postmodernis bahwa postmodernisme secara inheren apatis atau bermusuhan dengan tindakan sosial atau politik. Postmodernisme merupakan reaksi terhadap cita-cita epistemologis modernitas. Postmodernisme didasarkan pada sudut pandang manusia yang terbatas, dan dengan demikian menjadi tawanan subyektivitasnya sendiri, menghasilkan dua karakteristik utama, yaitu pluralisme dan relativisme. Kajian ini menganalisis pandangan postmodern yang diimplementasikan pada pendidikan Kristen di Indonesia. Metode yang digunakan pada artikel ini adalah studi literatur dengan memanfaat kacamata biblis filosofis untuk menganalisa pandangan postmodern. Hasilnya adalah pendidikan moral postmodern (seperti transendentalisme dan idealisme) memiliki beberapa aspek yang berguna dan beberapa negatif yang harus dipertimbangkan untuk perencanaan pendidikan moral dan pengembangan kurikulum pendidikan Kristen di Indonesia.